PENINGKATAN KETERAMPILAN MENYIMAK BAHAN AJAR DENGAN MENGGUNAKAN MEDIA AUDIO PADA SISWA SEKOLAH DASAR - Mahpudoh Mahpudoh; Desma Yuliadi Saputra; Julina Julina; Dewi Syifa Septiani (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
This study aims to improve students' listening skills using audio media, namely the use of audio media, such as playing learning materials through (speakers handphone) for students in grades V and VI at the elementary school level. This research is classroom action research which is carried out in three cycles. In the learning process there are two stages, namely, the planning stage and the implementation stage. The subjects in the study were students in grades V and VI of Elementary School who carried out Tutoring (bimbel) at the IC Privat Les (Iqro Corner) on Jl. KH. Abdul Latief No.47 Pecung Well, Serang City Banten, 42118. The results showed an increase in the average score of the final listening test after getting treatment on the effectiveness of using audio media from each cycle